2021
DOI: 10.1002/ps.6582
|View full text |Cite
|
Sign up to set email alerts
|

SlGSTE9 participates in the stability of chlorpyrifos resistance in Spodoptera litura

Abstract: BACKGROUND: Spodoptera litura is an important agricultural pest and has developed serious resistance to multiple insecticides. The resistance level to several insecticides is reported to be unstable, but the mechanism is less reported.RESULTS: Chlorpyrifos and phoxim resistance level in a field-collected population of S. litura declined continuously from the first to the tenth generation and remained stable at the 11th and 12th generations without insecticide exposure. Synergist experiment showed that diethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Spodoptera litura populations used in this study were described in Li, He, Xie, Ge, et al (2021). Briefly, GX population of S. litura , kindly provided by Guangxi Tianyuan Biochemistry Corp Ltd, served as a susceptible population.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spodoptera litura populations used in this study were described in Li, He, Xie, Ge, et al (2021). Briefly, GX population of S. litura , kindly provided by Guangxi Tianyuan Biochemistry Corp Ltd, served as a susceptible population.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA full length of SlGSTe8 was cloned and expressed in a prokaryotic expression system E. coli BL21 (DE3) (Tiangen). The heterologous expression of SlGSTE8 was conducted as described in Li, He, Xie, Ge, et al (2021). Briefly, restriction enzyme sites Nde I and Xho I were introduced to the cDNA full length of SlGSTe8 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SlGSTE9 with high expression abundance has also been shown to be involved in chlorpyrifos resistance in Spodoptera litura (Li et al. , 2021). In this study, CYP392A1 and TcGSTd05 were respectively found to have the highest upregulation fold change (697.7‐fold) and expression abundance (FPKM > 400) among all overexpressed detoxification enzyme genes in the 3 stages, suggesting they may also contribute to cyflumetofen resistance in the YN‐CyR strain.…”
Section: Discussionmentioning
confidence: 99%